New public management and health care in Third World - Bennett, Sara; Muraleedharan, V.R. (2000)
`New public management' (NPM) involves a shift from direct provision of services by government to such indirect modes as policy-making, regulation, co-ordination and contracting. Its proponents assert that its application has improved the way in which the governments of many industrialised countries do business. As for the third world, this paper argues through a case study of emerging trends in the health care sector in Tamil Nadu, that there are many constraints on government capacity to play the complex new roles associated with NPM. - Reproduced
Keywords: Health services; Public administration